Identifikasi Ujaran Kebencian Pada Facebook Dengan Metode Ensemble Feature Dan Support Vector Machine - Aditya Kresna Bayu Arda Putra; Mochammad Ali Fauzi; Budi Darma Setiawan; Eti Setiawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In the beginning, social media is used for socializing and interacting with other people. One of the most used social media for socializing is Facebook, with users amounting to over hundred million people around the world. Nowadays, on Facebook, its often found there's hate speech writing being shared at massive pace. Of course an assistance from language expert is a must for identifying hatespeech on Facebook because there's not yet an automatic system that can identify a hatespeech. The system in this research are made using Ensemble feature and Support Vector Machine. Ensemble feature is used for combining some of the feature extracted from each writing to ease the process of identifying a hatespeech. Support Vector Machine then used to identifying a hatespeech from a writing based on feature that are combined using ensemble feature. According to the result of testing, we acquired a 70% accuracy for the system so we can conclude that ensemble feature and support vector machine is good to use for identifying hatespeech on social media Facebook.